Array Design and Transmitter Coils Selection for Underwater Wireless Power Transfer System - Hanxi Xu; Wenhua Li; Zhongjiu Zheng; Yunhe Wang (Applied Sciences)
This paper proposes a method for array design and optimal transmitting coil selection of underwater wireless power transfer systems. This method is divided into three steps. Firstly, by analyzing the influence of different ratio side lengths of the transmitting coil and receiving coil on mutual inductance, the optimal ratio side length coil is selected. Secondly, by analyzing the relative size of the reflection impedance of the power supply coil and its surrounding coils, the optimal coil activation criterion is derived. Finally, by estimating the position of the receiving coil without communication, the switching of the power supply coil is realized. According to the proposed method, it was verified on the experimental platform. Under a rated power of 300 W with a load resistance of 20 Ω, the system maintains efficiency ≥ 80% even under horizontal offsets up to 150 mm (75% of the transmitting coil side length) and two-dimensional offsets up to 200 mm (100% of the transmitting coil side length).